THE EVALUATION OF CURRICULUM IMPLEMENTATION AT TARBIYAH FACULTY IAIN RADEN FATAH PALEMBANG - Fajri Ismail (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2015)
This research aims to figure out the facts of the objective conditions of the curriculum implementation at Tarbiyah Faculty IAIN Raden Fatah Palembang. The curriculum evaluation used the Evaluation Programme for Innovative Curriculum (EPIC) Model, consisting of three components namely: 1) instruction, 2) institutional, and 3) learning achievement. This research used an evaluative programme to make judgments and decisions of a programme or curriculum. The evaluation results for these three components are: (1) instruction: learning burdens and lecturers’ quality are good, but there are still many errors in the presentation, coding, credits of institutional courses, faculty courses, and study program courses, low in task variation, low in the number of hours of meetings, many mistakes in curriculum structure, and low in facilities and infrastructure, (2) institutional: entrance tests for the students of Tarbiyah Faculty IAIN Raden Fatah do not include aptitude tests, lecturers who have magister qualification is good, but low on doctoral qualification, and ratio between lecturers to students is not ideal, (3) learning achievement: students’ mastery of teaching skills and attitudes is good, but very low in the mastery of pedagogical skills and teacher education. Recommendations of this research are 1) revise curriculum, 2) use the aptitude test to select new students, 3) increase academic qualifications of lecturers, and 4) revise comprehensive examination system.